The Effect of PLS & NPLS Financing on the Industrial Production Index of The Indonesian Economy - Yanti, Eva Virda; Lubis, Firsty Ramadhona Amalia; Az zakiyyah, Nurul Azizah (Journal of Economics Research and Social Sciences, 2025)
This study aims to see the effect of PLS & non-PLS financing on Indonesia's economic growth using Autoregressive Distributed Lag (ARDL) with monthly data from January 2017 - December 2021. The results showed that financing with non-PLS schemes is still better in supporting the real sector than PLS schemes in the long term. For the short term, the second PLS and non-PLS financing schemes have a negative influence. Therefore, concrete steps must be taken to enhance PLS financing schemes to grow Islamic finance.